Copper-based catalyst as well as preparation method and application thereof
The copper-based catalyst is prepared by combining the impregnation method and the sol-gel method, and the problem of insufficient activity and mechanical strength of the copper-based catalyst in the prior art is solved, and an efficient methanol reforming hydrogen production process is achieved.
Patent Information
- Application Number
- CN202510490087.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-18
- Publication Date
- 2025-08-08
AI Technical Summary
The existing copper-based catalysts have problems such as low catalytic activity, poor mechanical strength, easy sintering and poisoning during the hydrogen production process of methanol reforming, and it is difficult to adapt to complex operating conditions.
The preparation method combined with impregnation method and sol-gel method is used to mix copper, zinc and aluminum precursors and add appropriate reagents to adjust the pH value, and a catalyst composed of copper oxide, zinc oxide and alumina is prepared, and then die-casted after drying and calcining to improve the mechanical strength and activity of the catalyst.
The prepared copper-based catalyst has high copper loading, high mechanical strength, and exhibits high catalytic activity and stability. It is suitable for methanol water vapor reforming, methanol self-heating reforming and water vapor transformation reactions.
Smart Images

Figure BDA0005365301410000181 
Figure BDA0005365301410000182 
Figure BDA0005365301410000191
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of catalyst preparation, and relates to a copper-based catalyst and a preparation method and application thereof. Background Art
[0002] Proton exchange membrane fuel cells (PEMFCs) fueled by hydrogen offer advantages such as low operating temperature, high energy conversion efficiency, and low carbon emissions, making them a promising new energy technology. However, hydrogen's flammability, explosiveness, and leakage susceptibility lead to safety risks in its storage and transportation, as well as high refueling costs, which limit the large-scale application of hydrogen fuel cells. Compared with compressed hydrogen, liquid ammonia, hydrogen storage alloys, and other organic hydrogen carriers, methanol offers advantages such as high hydrogen storage density, low pyrolysis temperature, improved safety, and the ability to fully utilize existing diesel and gasoline transportation infrastructure. Furthermore, methanol is widely available and can be produced from fossil fuels, making it considered "blue methanol." Biomass-to-methanol and liquid solar energy ("green hydrogen" produced by electrolysis of water using renewable energy sources such as photovoltaics and "green methanol" synthesized from carbon dioxide captured by coal-fired power plants) have further enriched methanol sources. A new and effective pathway for the large-scale commercial application of hydrogen energy is the methanol production-storage, transportation, and refueling-online hydrogen production-fuel cell approach. There are still some urgent problems to be solved in the online reforming of methanol to produce hydrogen to provide hydrogen source for fuel cells, such as long startup time, easy deactivation of catalysts, high CO concentration, low mechanical strength and poor stability.
[0003] Copper-based catalysts are highly active and economical, and are commonly used in methanol reforming to produce hydrogen and water-gas shift reactions. Existing copper-based catalysts are generally prepared using the traditional co-precipitation method. This method produces high copper loadings (typically 40-50 wt%) and uniformly mixes the catalyst components. However, these catalysts also suffer from shortcomings such as sintering at high temperatures, low mechanical strength, and a need for further improvement in low-temperature activity. The sol-gel method is still in the exploratory stage for preparing copper-based catalysts. The sol-gel method can produce uniform, high-purity oxide materials through a series of low-temperature operations. The sol-gel method eliminates the need for cleaning the catalyst material, significantly reducing wastewater generated during the catalyst preparation process. However, the sol-gel method is susceptible to gelation conditions such as gelation temperature and pH, and the powder is prone to forming hard agglomerates during calcination, reducing its activity. Copper-based catalysts prepared by the impregnation method exhibit high mechanical strength, but low copper loadings. In summary, existing copper-based catalysts suffer from poor activity stability, susceptibility to carbon deposition, poisoning, and sintering. When methanol is reformed online to produce hydrogen, copper-based catalysts will experience complex operating conditions such as frequent vibrations, sudden starts and stops. The operating temperature of existing copper-based catalysts is often higher than 280°C to achieve complete conversion of methanol. Copper-based catalysts face the risk of deactivation caused by high-temperature sintering and reduced mechanical strength.
[0004] In summary, new copper-based catalyst preparation technologies still need to be studied to obtain copper-based catalysts with high catalytic activity and high mechanical strength suitable for methanol reforming to produce hydrogen. Summary of the Invention
[0005] The object of the present invention is to provide a technical solution for a copper-based catalyst with high catalytic activity and high mechanical strength suitable for online reforming of methanol to produce hydrogen.
[0006] In order to achieve the above objectives, the present invention provides the following technical solutions.
[0007] In a first aspect, the present invention provides a method for preparing a copper-based catalyst, wherein the preparation method comprises:
[0008] 1) Mixing a copper precursor, a zinc precursor, an aluminum precursor, and water to prepare a sol solution or suspension; wherein the copper precursor is a copper metal salt, the zinc precursor is a zinc metal salt, and the aluminum precursor includes at least one of an aluminum metal salt and activated alumina particles;
[0009] 2) adding a first reagent to the sol solution or suspension prepared in step 1) and then adding a first regulator to adjust the pH value of the solution to 2-8, wherein the first reagent comprises at least one of citric acid, ammonium citrate, maleic acid, oxalic acid, and ammonium oxalate; the ratio of the molar amount of the first reagent to the sum of the molar amounts of copper, zinc, and aluminum is (1-3):1; and the first regulator comprises at least one of ammonia, ammonium carbonate, and ammonium bicarbonate;
[0010] 3) heating the neutral solution prepared in step 2) to react (by heating to evaporate the water solvent to induce a condensation reaction between the metal salt and the carboxyl group) to obtain a wet gel; then drying the wet gel to obtain a xerogel;
[0011] 4) calcining the xerogel prepared in step 3) to obtain catalyst powder;
[0012] 5) The catalyst powder is die-cast and then calcined to obtain the copper-based catalyst.
[0013] The technical solution of the present invention combines the impregnation method and the sol-gel method to prepare a copper-based catalyst. The active component of the prepared copper-based catalyst is copper oxide, the auxiliary agent is zinc oxide, and the carrier is aluminum oxide. The prepared copper-based catalyst is used for online methanol reforming to produce hydrogen and exhibits high mechanical strength, high catalytic activity, and high catalytic stability.
[0014] According to a specific embodiment of the first aspect, preferably, the copper precursor, the zinc precursor, the aluminum precursor and water are mixed to prepare a sol solution or a suspension by one of the following methods:
[0015] Method 1: copper metal salt, zinc metal salt and aluminum metal salt are added into water to form a sol solution;
[0016] In this method, the aluminum precursor is an aluminum metal salt;
[0017] Method 2: copper metal salt, zinc metal salt, and aluminum metal salt are added to water to form a sol solution; activated alumina particles are added to the sol solution to obtain a suspension;
[0018] In this method, the aluminum precursor includes aluminum metal salt and activated alumina particles. The carrier alumina in the prepared copper-based catalyst is composed of two parts, one part comes from the oxidative decomposition of the aluminum metal salt or its complex, and the other part comes from the directly added activated alumina particles. In a further preferred embodiment, based on the total mass of aluminum in the aluminum precursor being 100%, the mass proportion of aluminum in the activated alumina particles is 30-70%.
[0019] Method 3: copper metal salt and zinc metal salt are added to water to form a sol solution; activated alumina particles are added to the sol solution to obtain a suspension;
[0020] In this method, the aluminum precursor is activated alumina particles.
[0021] According to a specific embodiment of the first aspect, preferably, the copper metal salt includes but is not limited to one or a combination of two or more of copper nitrate, copper sulfate, copper chloride, copper citrate, and copper acetate.
[0022] According to a specific embodiment of the first aspect, preferably, the zinc metal salt includes but is not limited to one or a combination of two or more of zinc nitrate, zinc sulfate, zinc chloride, zinc citrate, and zinc acetate.
[0023] According to a specific embodiment of the first aspect, preferably, the aluminum metal salt includes but is not limited to one or a combination of two or more of aluminum nitrate, aluminum sulfate, aluminum chloride, aluminum citrate, and aluminum acetate.
[0024] According to a specific embodiment of the first aspect, preferably, the median particle size D of the activated alumina particles is 50 6.0μm-30μm.
[0025] According to a specific embodiment of the first aspect, preferably, the molar ratio of copper, zinc and aluminum in the copper precursor, the zinc precursor and the aluminum precursor is 1:(0.33-1.67):(0.24-0.72).
[0026] According to a specific embodiment of the first aspect, preferably, the ratio of the molar amount of the first reagent to the sum of the molar amounts of copper, zinc and aluminum is 1.5:1.
[0027] According to a specific embodiment of the first aspect, preferably, the adding of the first reagent is performed by adding an aqueous solution of the first reagent;
[0028] More preferably, based on the mass of the aqueous solution of the first reagent being 100%, the mass concentration of the first reagent in the aqueous solution of the first reagent is 15%-45%.
[0029] According to a specific embodiment of the first aspect, preferably, a first regulator is added to adjust the pH value of the solution to 7.
[0030] According to a specific embodiment of the first aspect, preferably, the first regulator is added by adding an aqueous solution of the first regulator;
[0031] More preferably, based on the mass of the aqueous solution of the first regulator being 100%, the concentration of the first regulator in the aqueous solution of the first regulator is 7%-14%.
[0032] According to a specific embodiment of the first aspect, preferably, the temperature of the neutral solution for heating the reaction is 60-80°C.
[0033] According to a specific embodiment of the first aspect, preferably, the wet gel is dried at 100° C.-110° C.;
[0034] More preferably, the drying time is 8h-24h.
[0035] According to a specific embodiment of the first aspect, preferably, during the calcination of the dry gel, the calcination temperature is 250-500°C; more preferably, during the calcination of the dry gel, the calcination temperature is 350°C;
[0036] More preferably, the calcination time is 8h-24h.
[0037] According to a specific embodiment of the first aspect, preferably, during the calcination of the dry gel, the calcination atmosphere is an air atmosphere.
[0038] According to a specific embodiment of the first aspect, preferably, the catalyst powder die-casting is achieved by the following method:
[0039] mixing the catalyst powder with water or polyvinyl alcohol solution to obtain a mixed material;
[0040] Die-casting the mixed material into a shape;
[0041] More preferably, the concentration of polyvinyl alcohol in the polyvinyl alcohol solution is 1.5-4%, based on the total mass of the polyvinyl alcohol solution being 100%;
[0042] More preferably, the mass ratio of water or polyvinyl alcohol solution to catalyst powder is 1:(24-49);
[0043] More preferably, during the die-casting process of the mixed material, the pressing pressure is 10-20 MPa;
[0044] More preferably, during the die-casting process of the mixed material, the pressing time is 1-3 minutes;
[0045] More preferably, the mixed material is die-casted into a cylindrical shape having a diameter of 2-4 cm and a height of 1-2 cm.
[0046] According to a specific embodiment of the first aspect, preferably, during the calcination process of the catalyst powder after die-casting, the calcination temperature is 250-500°C; more preferably, during the calcination process of the dry gel, the calcination temperature is 350°C;
[0047] More preferably, the calcination time is 8-24 hours.
[0048] According to a specific embodiment of the first aspect, preferably, during the calcination process of the catalyst powder after die-casting, the calcination atmosphere is an air atmosphere.
[0049] In a second aspect, the present invention provides a copper-based catalyst, wherein the copper-based catalyst can be prepared by the preparation method of the copper-based catalyst provided in the first aspect of the invention.
[0050] In a third aspect, the present invention provides the use of a copper-based catalyst as a catalyst in methanol steam reforming, methanol autothermal reforming, and water gas shift reactions, wherein the copper-based catalyst is the copper-based catalyst provided in the second aspect of the invention.
[0051] According to a specific embodiment of the third aspect, preferably, in the methanol steam reforming reaction, the water-to-alcohol ratio of the methanol aqueous solution used is 1-2, the liquid phase space velocity is 0.5-2.5 / h, and the reaction temperature is 160-260°C;
[0052] More preferably, in the methanol steam reforming reaction, the water-to-methanol ratio of the methanol aqueous solution used is 1.5, the liquid phase space velocity is 1.5 / h, and the reaction temperature is 220°C.
[0053] According to a specific embodiment of the third aspect, preferably, in the water gas shift reaction, the gas space velocity is 1000-2500 / h and the reaction temperature is 160-240°C;
[0054] More preferably, in the water gas shift reaction, the gas space velocity is 1500 / h and the reaction temperature is 200°C.
[0055] According to a specific embodiment of the third aspect, preferably, in the methanol autothermal reforming reaction, the water-to-methanol ratio is 0-1.5, the liquid phase space velocity is 1.0-3.0 / h, and the oxygen-to-methanol molar ratio is 0.3-0.6;
[0056] More preferably, in the methanol autothermal reforming reaction, the oxygen to methanol molar ratio is 0.4, the water to methanol ratio is 1.5, and the liquid phase space velocity is 2.0 / h.
[0057] Compared with the prior art, the technical solution provided by the present invention has the following beneficial effects:
[0058] 1. The preparation method of the copper-based catalyst provided by the present invention is to prepare the copper-based catalyst by combining the impregnation method with the sol-gel method. The preparation method maintains a high copper loading and catalytic activity, and the copper loading can reach 30-60wt%.
[0059] 2. The copper-based catalyst provided by the technical solution of the present invention has a high crushing strength, which can reach 37.5N / mm.
[0060] 3. The copper-based catalyst provided by the technical solution of the present invention exhibits high catalytic activity, selectivity and stability in methanol steam reforming (MSR), methanol autothermal reforming (ATR) and water gas shift (WGS) reactions. BRIEF DESCRIPTION OF THE DRAWINGS
[0061] Figure 1 The ATR tail gas composition diagram on MCZA-5 at different oxygen-methanol molar ratios.
[0062] Figure 2 This is the result of long-term WGS operation on copper-based catalysts.
[0063] Figure 3 This is the average crushing strength diagram of copper-based catalysts. DETAILED DESCRIPTION
[0064] To make the objectives, technical solutions, and advantages of the embodiments of the present invention more clear, the technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative efforts are within the scope of protection of the present invention.
[0065] Example 1
[0066] This example provides a copper-based catalyst CZA-1.
[0067] The copper-based catalyst CZA-1 comprises an active component, a coagent, and a carrier. The active component is copper oxide, the coagent is zinc oxide, and the carrier is aluminum oxide. The precursors of each component are chelated in a gel, then dried, calcined, and die-cast to produce the copper-based catalyst. The molar ratio of Cu:Zn:Al in the copper-based catalyst CZA-1 is approximately 3:5:2. It is prepared by the following method:
[0068] 1) Weigh 36.24 g, 73.08 g, and 36.78 g of copper nitrate trihydrate, zinc nitrate hexahydrate, and aluminum nitrate nonahydrate, respectively, and dissolve them in 200 ml of deionized water to form a sol solution;
[0069] 2) Weigh 142.30 g of citric acid and dissolve it in 500 ml of deionized water to form a citric acid solution;
[0070] 3) obtaining a certain amount of ammonia water with an ammonia concentration of 28 wt % through a pipette and diluting it to an ammonia concentration of 7 wt %;
[0071] 4) placing the sol solution obtained in step 1) in a water bath at 80° C. and continuously stirring and heating, while slowly adding the citric acid solution obtained in step 2) and then adding the ammonia solution obtained in step 3) to adjust the solution pH to 7;
[0072] 5) The solution obtained in step 4) was heated in a water bath at 80° C. with continuous stirring for more than 4 hours to react to obtain a wet gel;
[0073] 6) placing the wet gel obtained in step 5) in a constant temperature drying oven at 105° C. and drying for 12 hours to obtain a dry gel;
[0074] 7) calcining the xerogel obtained in step 6) in a muffle furnace at 350° C. for 3 h to obtain a catalyst powder;
[0075] 8) mixing the catalyst powder obtained in step 7) with a polyvinyl alcohol solution having a polyvinyl alcohol concentration of 2 wt % in a mass ratio of 49:1 to obtain a mixed powder;
[0076] 9) The mixed powder obtained in step 8) was pressed into a cylindrical shape on a tablet press (pressure of 20 MPa, holding time of 2 min, the catalyst shape was a cylinder with a diameter of 3 cm and a height of 1 cm);
[0077] 10) The cylindrical catalyst obtained in step 9) was placed in a muffle furnace at 350° C. and calcined for 3 h to obtain a copper-based catalyst CZA-1.
[0078] Example 2
[0079] This example provides a copper-based catalyst CZA-2.
[0080] The copper-based catalyst CZA-2 comprises an active component, an auxiliary agent, and a carrier. The active component is copper oxide, the auxiliary agent is zinc oxide, and the carrier is aluminum oxide. The precursors of each component are chelated in a gel, then dried, calcined, and die-cast to produce the copper-based catalyst. The molar ratio of Cu:Zn:Al in the copper-based catalyst CZA-2 is approximately 4:4:2. It is prepared by the following method:
[0081] 1) Weigh 38.96 g, 47.5 g, and 30.16 g of copper nitrate trihydrate, zinc nitrate hexahydrate, and aluminum nitrate nonahydrate, respectively, and dissolve them in 200 ml of deionized water to form a sol solution;
[0082] 2) Weigh 115.67 g of citric acid and dissolve it in 500 ml of deionized water to form a citric acid solution;
[0083] 3) obtaining a certain amount of ammonia water with an ammonia concentration of 28 wt % through a pipette and diluting it to an ammonia concentration of 7 wt %;
[0084] 4) placing the sol solution obtained in step 1) in a water bath at 80° C. and continuously stirring and heating, while slowly adding the citric acid solution obtained in step 2) and then adding the ammonia solution obtained in step 3) to adjust the solution pH to 7;
[0085] 5) The solution obtained in step 4) was heated in a water bath at 80° C. with continuous stirring for more than 4 hours to react to obtain a wet gel;
[0086] 6) placing the wet gel obtained in step 5) in a constant temperature drying oven at 105° C. and drying for 12 hours to obtain a dry gel;
[0087] 7) calcining the xerogel obtained in step 6) in a muffle furnace at 350° C. for 3 h to obtain a catalyst powder;
[0088] 8) mixing the catalyst powder obtained in step 7) with a polyvinyl alcohol solution having a polyvinyl alcohol concentration of 2 wt % in a mass ratio of 49:1 to obtain a mixed powder;
[0089] 9) The mixed powder obtained in step 8) was pressed into a cylindrical shape on a tablet press (pressure of 20 MPa, holding time of 2 min, the catalyst shape was a cylinder with a diameter of 3 cm and a height of 1 cm);
[0090] 10) The cylindrical catalyst obtained in step 9) was placed in a muffle furnace at 350° C. and calcined for 3 h to obtain a copper-based catalyst CZA-2.
[0091] Example 3
[0092] This example provides a copper-based catalyst CZA-3.
[0093] The copper-based catalyst CZA-3 comprises an active component, an additive, and a carrier. The active component is copper oxide, the additive is zinc oxide, and the carrier is aluminum oxide. The precursors of each component are chelated in a gel, then dried, calcined, and die-cast to produce the copper-based catalyst. The molar ratio of Cu:Zn:Al in the copper-based catalyst CZA-3 is approximately 5:3:2. It is prepared by the following method:
[0094] 1) Weigh 65.23 g, 48.24 g, and 40.46 g of copper nitrate trihydrate, zinc nitrate hexahydrate, and aluminum nitrate nonahydrate, respectively, and dissolve them in 200 ml of deionized water to form a sol solution;
[0095] 2) Weigh 155.63 g of citric acid and dissolve it in 500 ml of deionized water to form a citric acid solution;
[0096] 3) obtaining a certain amount of ammonia water with an ammonia concentration of 28 wt % through a pipette and diluting it to an ammonia concentration of 7 wt %;
[0097] 4) placing the sol solution obtained in step 1) in a water bath at 80° C. and continuously stirring and heating, while slowly adding the citric acid solution obtained in step 2) and then adding the ammonia solution obtained in step 3) to adjust the solution pH to 7;
[0098] 5) The solution obtained in step 4) was heated in a water bath at 80° C. with continuous stirring for more than 4 hours to react to obtain a wet gel;
[0099] 6) placing the wet gel obtained in step 5) in a constant temperature drying oven at 105° C. and drying for 12 hours to obtain a dry gel;
[0100] 7) calcining the xerogel obtained in step 6) in a muffle furnace at 350° C. for 3 h to obtain a catalyst powder;
[0101] 8) mixing the catalyst powder obtained in step 7) with a polyvinyl alcohol solution having a polyvinyl alcohol concentration of 2 wt % in a mass ratio of 49:1 to obtain a mixed powder;
[0102] 9) The mixed powder obtained in step 8) was pressed into a cylindrical shape on a tablet press (pressure of 20 MPa, holding time of 2 min, the catalyst shape was a cylinder with a diameter of 3 cm and a height of 1 cm);
[0103] 10) The cylindrical catalyst obtained in step 9) was placed in a muffle furnace at 350° C. and calcined for 3 h to obtain a copper-based catalyst CZA-3.
[0104] Example 4
[0105] This example provides a copper-based catalyst CZA-4.
[0106] The copper-based catalyst CZA-4 comprises an active component, a coagent, and a carrier. The active component is copper oxide, the coagent is zinc oxide, and the carrier is aluminum oxide. The precursors of each component are chelated in a gel, then dried, calcined, and die-cast to produce the copper-based catalyst. The molar ratio of Cu:Zn:Al in the copper-based catalyst CZA-4 is approximately 6:2:2. It is prepared by the following method:
[0107] 1) Weigh 62.26 g, 25.58 g, and 32.25 g of copper nitrate trihydrate, zinc nitrate hexahydrate, and aluminum nitrate nonahydrate, respectively, and dissolve them in 200 ml of deionized water to form a sol solution;
[0108] 2) Weigh 115.67 g of citric acid and dissolve it in 500 ml of deionized water to form a citric acid solution;
[0109] 3) obtaining a certain amount of ammonia water with an ammonia concentration of 28 wt % through a pipette and diluting it to an ammonia concentration of 7 wt %;
[0110] 4) placing the sol solution obtained in step 1) in a water bath at 80° C. and continuously stirring and heating, while slowly adding the citric acid solution obtained in step 2) and then adding the ammonia solution obtained in step 3) to adjust the solution pH to 7;
[0111] 5) The solution obtained in step 4) was heated in a water bath at 80° C. with continuous stirring for more than 4 hours to react to obtain a wet gel;
[0112] 6) placing the wet gel obtained in step 5) in a constant temperature drying oven at 105° C. and drying for 12 hours to obtain a dry gel;
[0113] 7) calcining the xerogel obtained in step 6) in a muffle furnace at 350° C. for 3 h to obtain a catalyst powder;
[0114] 8) mixing the catalyst powder obtained in step 7) with a polyvinyl alcohol solution having a polyvinyl alcohol concentration of 2 wt % in a mass ratio of 49:1 to obtain a mixed powder;
[0115] 9) The mixed powder obtained in step 8) was pressed into a cylindrical shape on a tablet press (pressure of 20 MPa, holding time of 2 min, the catalyst shape was a cylinder with a diameter of 3 cm and a height of 1 cm);
[0116] 10) The cylindrical catalyst obtained in step 9) was placed in a muffle furnace at 350° C. and calcined for 3 h to obtain a copper-based catalyst CZA-4.
[0117] Example 5
[0118] This example provides a copper-based catalyst MCZA-1.
[0119] The copper-based catalyst MCZA-1 comprises an active component, an additive, and a carrier. The active component is copper oxide, the additive is zinc oxide, and the carrier is aluminum oxide. The precursors of each component are chelated in a gel, dried, calcined, and die-cast to produce the copper-based catalyst. The molar ratio of Cu:Zn:Al in the copper-based catalyst MCZA-1 is approximately 5:3:2, and the added activated aluminum oxide particles account for 30% of the total aluminum oxide mole fraction in the copper-based catalyst MCZA-1. The catalyst is prepared by the following method:
[0120] 1) Weigh 65.23 g, 48.24 g and 28.32 g of copper nitrate trihydrate, zinc nitrate hexahydrate and aluminum nitrate nonahydrate respectively and dissolve them in 200 ml of deionized water to form a sol solution; weigh 1.65 g of activated alumina (γ-Al2O3) particles (medium particle size D 50 6 μm), and slowly added it to the above sol solution which was constantly stirred to obtain a suspension;
[0121] 2) Weigh 248.58 g of citric acid and dissolve it in 500 ml of deionized water to form a citric acid solution;
[0122] 3) obtaining a certain amount of ammonia water with an ammonia concentration of 28 wt % through a pipette and diluting it to an ammonia concentration of 7 wt %;
[0123] 4) placing the suspension obtained in step 1) in a water bath at 80° C. and stirring continuously while heating, while slowly adding the citric acid solution obtained in step 2) and then adding the ammonia solution obtained in step 3) to adjust the pH of the solution to 7;
[0124] 5) The solution obtained in step 4) was heated in a water bath at 80° C. with continuous stirring for more than 4 hours to react to obtain a wet gel;
[0125] 6) placing the wet gel obtained in step 5) in a constant temperature drying oven at 105° C. and drying for 12 hours to obtain a dry gel;
[0126] 7) calcining the xerogel obtained in step 6) in a muffle furnace at 350° C. for 3 h to obtain a catalyst powder;
[0127] 8) mixing the catalyst powder obtained in step 7) with a polyvinyl alcohol solution having a polyvinyl alcohol concentration of 2 wt % in a mass ratio of 49:1 to obtain a mixed powder;
[0128] 9) The mixed powder obtained in step 8) was pressed into a cylindrical shape on a tablet press (pressure of 20 MPa, holding time of 2 min, the catalyst shape was a cylinder with a diameter of 3 cm and a height of 1 cm);
[0129] 10) The cylindrical catalyst obtained in step 9) was placed in a muffle furnace at 350° C. and calcined for 3 h to obtain the copper-based catalyst MCZA-1.
[0130] Example 6
[0131] This example provides a copper-based catalyst MCZA-2.
[0132] The copper-based catalyst MCZA-2 comprises an active component, an additive, and a carrier. The active component is copper oxide, the additive is zinc oxide, and the carrier is aluminum oxide. The precursors of each component are chelated in a gel, dried, calcined, and die-cast to produce the copper-based catalyst. The molar ratio of Cu:Zn:Al in the copper-based catalyst MCZA-2 is approximately 5:3:2, and the added activated aluminum oxide particles account for 50% of the total aluminum oxide mole fraction in the copper-based catalyst MCZA-2. The catalyst is prepared by the following method:
[0133] 1) Weigh 65.23 g, 48.24 g and 20.23 g of copper nitrate trihydrate, zinc nitrate hexahydrate and aluminum nitrate nonahydrate respectively and dissolve them in 200 ml of deionized water to form a sol solution; weigh 2.75 g of activated alumina (γ-Al2O3) particles (medium particle size D 50 6 μm), and slowly added it to the above sol solution which was constantly stirred to obtain a suspension;
[0134] 2) Weigh 248.58 g of citric acid and dissolve it in 500 ml of deionized water to form a citric acid solution;
[0135] 3) obtaining a certain amount of ammonia water with an ammonia concentration of 28 wt % through a pipette and diluting it to an ammonia concentration of 7 wt %;
[0136] 4) placing the suspension obtained in step 1) in a water bath at 80° C. and stirring continuously while heating, while slowly adding the citric acid solution obtained in step 2) and then adding the ammonia solution obtained in step 3) to adjust the pH of the solution to 7;
[0137] 5) The solution obtained in step 4) was heated in a water bath at 80° C. with continuous stirring for more than 4 hours to react to obtain a wet gel;
[0138] 6) placing the wet gel obtained in step 5) in a constant temperature drying oven at 105° C. and drying for 12 hours to obtain a dry gel;
[0139] 7) calcining the xerogel obtained in step 6) in a muffle furnace at 350° C. for 3 h to obtain a catalyst powder;
[0140] 8) mixing the catalyst powder obtained in step 7) with a polyvinyl alcohol solution having a polyvinyl alcohol concentration of 2 wt % in a mass ratio of 49:1 to obtain a mixed powder;
[0141] 9) The mixed powder obtained in step 8) was pressed into a cylindrical shape on a tablet press (pressure of 20 MPa, holding time of 2 min, the catalyst shape was a cylinder with a diameter of 3 cm and a height of 1 cm);
[0142] 10) The cylindrical catalyst obtained in step 9) was placed in a muffle furnace at 350° C. and calcined for 3 h to obtain the copper-based catalyst MCZA-2.
[0143] Example 7
[0144] This example provides a copper-based catalyst MCZA-3.
[0145] The copper-based catalyst MCZA-3 comprises an active component, an additive, and a carrier. The active component is copper oxide, the additive is zinc oxide, and the carrier is aluminum oxide. The precursors of each component are chelated in a gel, dried, calcined, and die-cast to produce the copper-based catalyst. The molar ratio of Cu:Zn:Al in the copper-based catalyst MCZA-3 is approximately 5:3:2, and the added activated aluminum oxide particles account for 70% of the total aluminum oxide mole fraction in the copper-based catalyst MCZA-3. The catalyst is prepared by the following method:
[0146] 1) Weigh 65.23 g, 48.24 g and 12.14 g of copper nitrate trihydrate, zinc nitrate hexahydrate and aluminum nitrate nonahydrate respectively and dissolve them in 200 ml of deionized water to form a sol solution; weigh 3.85 g of activated alumina (γ-Al2O3) particles (medium particle size D 50 6 μm), and slowly added it to the above sol solution which was constantly stirred to obtain a suspension;
[0147] 2) Weigh 248.58 g of citric acid and dissolve it in 500 ml of deionized water to form a citric acid solution;
[0148] 3) obtaining a certain amount of ammonia water with an ammonia concentration of 28 wt % through a pipette and diluting it to an ammonia concentration of 7 wt %;
[0149] 4) placing the suspension obtained in step 1) in a water bath at 80° C. and stirring continuously while heating, while slowly adding the citric acid solution obtained in step 2) and then adding the ammonia solution obtained in step 3) to adjust the pH of the solution to 7;
[0150] 5) The solution obtained in step 4) was heated in a water bath at 80° C. with continuous stirring for more than 4 hours to react to obtain a wet gel;
[0151] 6) placing the wet gel obtained in step 5) in a constant temperature drying oven at 105° C. and drying for 12 hours to obtain a dry gel;
[0152] 7) calcining the xerogel obtained in step 6) in a muffle furnace at 350° C. for 3 h to obtain a catalyst powder;
[0153] 8) mixing the catalyst powder obtained in step 7) with a polyvinyl alcohol solution having a polyvinyl alcohol concentration of 2 wt % in a mass ratio of 49:1 to obtain a mixed powder;
[0154] 9) The mixed powder obtained in step 8) was pressed into a cylindrical shape on a tablet press (pressure of 20 MPa, holding time of 2 min, the catalyst shape was a cylinder with a diameter of 3 cm and a height of 1 cm);
[0155] 10) The cylindrical catalyst obtained in step 9) was placed in a muffle furnace at 350° C. and calcined for 3 h to obtain the copper-based catalyst MCZA-3.
[0156] Example 8
[0157] This example provides a copper-based catalyst MCZA-4.
[0158] The copper-based catalyst MCZA-4 comprises an active component, an additive, and a carrier. The active component is copper oxide, the additive is zinc oxide, and the carrier is aluminum oxide. The precursors of each component are chelated in a gel, dried, calcined, and die-cast to obtain the copper-based catalyst. The molar ratio of Cu:Zn:Al in the copper-based catalyst MCZA-4 is 5:3:1.2, and the added activated aluminum oxide particles account for 100% of the total aluminum oxide mole fraction in the copper-based catalyst MCZA-4. The catalyst is prepared by the following method:
[0159] 1) Weigh 65.23g of copper nitrate trihydrate and 48.24g of zinc nitrate hexahydrate respectively and dissolve them in 200ml of deionized water to form a sol solution; weigh 3.33g of activated alumina (γ-Al2O3) particles (medium particle size D 50 6 μm), and slowly added it to the above sol solution which was constantly stirred to obtain a suspension;
[0160] 2) Weigh 124.55 g of citric acid and dissolve it in 500 ml of deionized water to form a citric acid solution;
[0161] 3) obtaining a certain amount of ammonia water with an ammonia concentration of 28 wt % through a pipette and diluting it to an ammonia concentration of 7 wt %;
[0162] 4) placing the suspension obtained in step 1) in a water bath at 80° C. and stirring continuously while heating, while slowly adding the citric acid solution obtained in step 2) and then adding the ammonia solution obtained in step 3) to adjust the pH of the solution to 7;
[0163] 5) The solution obtained in step 4) was heated in a water bath at 80° C. with continuous stirring for more than 4 hours to react to obtain a wet gel;
[0164] 6) placing the wet gel obtained in step 5) in a constant temperature drying oven at 105° C. and drying for 12 hours to obtain a dry gel;
[0165] 7) calcining the xerogel obtained in step 6) in a muffle furnace at 350° C. for 3 h to obtain a catalyst powder;
[0166] 8) mixing the catalyst powder obtained in step 7) with a polyvinyl alcohol solution having a polyvinyl alcohol concentration of 2 wt % in a mass ratio of 49:1 to obtain a mixed powder;
[0167] 9) The mixed powder obtained in step 8) was pressed into a cylindrical shape on a tablet press (pressure of 20 MPa, holding time of 2 min, the catalyst shape was a cylinder with a diameter of 3 cm and a height of 1 cm);
[0168] 10) The cylindrical catalyst obtained in step 9) was placed in a muffle furnace at 350° C. and calcined for 3 h to obtain the copper-based catalyst MCZA-4.
[0169] Example 9
[0170] This example provides a copper-based catalyst MCZA-5.
[0171] The copper-based catalyst MCZA-5 comprises an active component, an additive, and a carrier. The active component is copper oxide, the additive is zinc oxide, and the carrier is aluminum oxide. The precursors of each component are chelated in a gel, dried, calcined, and die-cast to produce the copper-based catalyst. The molar ratio of Cu:Zn:Al in the copper-based catalyst MCZA-5 is approximately 5:3:2, and the added activated aluminum oxide particles account for 100% of the total aluminum oxide mole fraction in the copper-based catalyst MCZA-5. The catalyst is prepared by the following method:
[0172] 1) Weigh 65.23g of copper nitrate trihydrate and 48.24g of zinc nitrate hexahydrate respectively and dissolve them in 200ml of deionized water to form a sol solution; weigh 5.5g of activated alumina (γ-Al2O3) particles (medium particle size D 50 6 μm), and slowly added it to the above sol solution which was constantly stirred to obtain a suspension;
[0173] 2) Weigh 124.55 g of citric acid and dissolve it in 500 ml of deionized water to form a citric acid solution;
[0174] 3) obtaining a certain amount of ammonia water with an ammonia concentration of 28 wt % through a pipette and diluting it to an ammonia concentration of 7 wt %;
[0175] 4) placing the suspension obtained in step 1) in a water bath at 80° C. and stirring continuously while heating, while slowly adding the citric acid solution obtained in step 2) and then adding the ammonia solution obtained in step 3) to adjust the pH of the solution to 7;
[0176] 5) The solution obtained in step 4) was heated in a water bath at 80° C. with continuous stirring for more than 4 hours to react to obtain a wet gel;
[0177] 6) placing the wet gel obtained in step 5) in a constant temperature drying oven at 105° C. and drying for 12 hours to obtain a dry gel;
[0178] 7) calcining the xerogel obtained in step 6) in a muffle furnace at 350° C. for 3 h to obtain a catalyst powder;
[0179] 8) mixing the catalyst powder obtained in step 7) with a polyvinyl alcohol solution having a polyvinyl alcohol concentration of 2 wt % in a mass ratio of 49:1 to obtain a mixed powder;
[0180] 9) The mixed powder obtained in step 8) was pressed into a cylindrical shape on a tablet press (pressure of 20 MPa, holding time of 2 min, the catalyst shape was a cylinder with a diameter of 3 cm and a height of 1 cm);
[0181] 10) The cylindrical catalyst obtained in step 9) was placed in a muffle furnace at 350° C. and calcined for 3 h to obtain the copper-based catalyst MCZA-5.
[0182] Example 10
[0183] This example provides a copper-based catalyst MCZA-6.
[0184] The copper-based catalyst MCZA-6 comprises an active component, an additive, and a carrier. The active component is copper oxide, the additive is zinc oxide, and the carrier is aluminum oxide. The precursors of each component are chelated in a gel, dried, calcined, and die-cast to obtain the copper-based catalyst. The molar ratio of Cu:Zn:Al in the copper-based catalyst MCZA-6 is approximately 5:3:2.8, and the added activated aluminum oxide particles account for 100% of the total aluminum oxide mole fraction in the copper-based catalyst MCZA-6. The catalyst is prepared by the following method:
[0185] 1) Weigh 63.12g of copper nitrate trihydrate and 46.77g of zinc nitrate hexahydrate respectively and dissolve them in 200ml of deionized water to form a sol solution; weigh 7.4g of activated alumina (γ-Al2O3) particles (medium particle size D 50 6 μm), and slowly added it to the above sol solution which was constantly stirred to obtain a suspension;
[0186] 2) Weigh 120.61 g of citric acid and dissolve it in 500 ml of deionized water to form a citric acid solution;
[0187] 3) obtaining a certain amount of ammonia water with an ammonia concentration of 28 wt % through a pipette and diluting it to an ammonia concentration of 7 wt %;
[0188] 4) placing the suspension obtained in step 1) in a water bath at 80° C. and stirring continuously while heating, while slowly adding the citric acid solution obtained in step 2) and then adding the ammonia solution obtained in step 3) to adjust the pH of the solution to 7;
[0189] 5) The solution obtained in step 4) was heated in a water bath at 80° C. with continuous stirring for more than 4 hours to react to obtain a wet gel;
[0190] 6) placing the wet gel obtained in step 5) in a constant temperature drying oven at 105° C. and drying for 12 hours to obtain a dry gel;
[0191] 7) calcining the xerogel obtained in step 6) in a muffle furnace at 350° C. for 3 h to obtain a catalyst powder;
[0192] 8) mixing the catalyst powder obtained in step 7) with a polyvinyl alcohol solution having a polyvinyl alcohol concentration of 2 wt % in a mass ratio of 49:1 to obtain a mixed powder;
[0193] 9) The mixed powder obtained in step 8) was pressed into a cylindrical shape on a tablet press (pressure of 20 MPa, holding time of 2 min, the catalyst shape was a cylinder with a diameter of 3 cm and a height of 1 cm);
[0194] 10) The cylindrical catalyst obtained in step 9) was placed in a muffle furnace at 350° C. and calcined for 3 h to obtain the copper-based catalyst MCZA-6.
[0195] Example 11
[0196] This example provides a copper-based catalyst MCZA-7.
[0197] The copper-based catalyst MCZA-7 comprises an active component, an additive, and a carrier. The active component is copper oxide, the additive is zinc oxide, and the carrier is aluminum oxide. The precursors of each component are chelated in a gel, dried, calcined, and die-cast to produce the copper-based catalyst. The molar ratio of Cu:Zn:Al in the copper-based catalyst MCZA-7 is approximately 5:3:3.6, and the added activated aluminum oxide particles account for 100% of the total aluminum oxide mole fraction in the copper-based catalyst MCZA-7. The catalyst is prepared by the following method:
[0198] 1) Weigh 63.12g of copper nitrate trihydrate and 46.77g of zinc nitrate hexahydrate respectively and dissolve them in 200ml of deionized water to form a sol solution; weigh 9.6g of activated alumina (γ-Al2O3) particles (medium particle size D 50 6 μm), and slowly added it to the above sol solution which was constantly stirred to obtain a suspension;
[0199] 2) Weigh 120.61 g of citric acid and dissolve it in 500 ml of deionized water to form a citric acid solution;
[0200] 3) obtaining a certain amount of ammonia water with an ammonia concentration of 28 wt % through a pipette and diluting it to an ammonia concentration of 7 wt %;
[0201] 4) placing the suspension obtained in step 1) in a water bath at 80° C. and stirring continuously while heating, while slowly adding the citric acid solution obtained in step 2) and then adding the ammonia solution obtained in step 3) to adjust the pH of the solution to 7;
[0202] 5) The solution obtained in step 4) was heated in a water bath at 80° C. with continuous stirring for more than 4 hours to react to obtain a wet gel;
[0203] 6) placing the wet gel obtained in step 5) in a constant temperature drying oven at 105° C. and drying for 12 hours to obtain a dry gel;
[0204] 7) calcining the xerogel obtained in step 6) in a muffle furnace at 350° C. for 3 h to obtain a catalyst powder;
[0205] 8) mixing the catalyst powder obtained in step 7) with a polyvinyl alcohol solution having a polyvinyl alcohol concentration of 2 wt % in a mass ratio of 49:1 to obtain a mixed powder;
[0206] 9) The mixed powder obtained in step 8) was pressed into a cylindrical shape on a tablet press (pressure of 20 MPa, holding time of 2 min, the catalyst shape was a cylinder with a diameter of 3 cm and a height of 1 cm);
[0207] 10) The cylindrical catalyst obtained in step 9) was placed in a muffle furnace at 350° C. and calcined for 3 h to obtain the copper-based catalyst MCZA-7.
[0208] Experimental Example 1
[0209] This experimental example is used to test the mechanical strength of the copper-based catalysts provided in Examples 1 to 11, the copper-based catalyst CZA-S1 (CO conversion catalyst of Sichuan Yalian High-tech Co., Ltd.), the copper-based catalyst CZA-S2 (methanol reforming catalyst of Sichuan Yalian High-tech Co., Ltd.), and the copper-based catalyst CZA-S3 (methanol reforming catalyst SCST401 of Sichuan Shutai Chemical Technology Co., Ltd.).
[0210] The mechanical strength of the copper-based catalysts provided in Examples 1 to 11 (composition see Table 1), the copper-based catalysts provided in Examples 1 to 11, the copper-based catalysts CZA-S1, the copper-based catalyst CZA-S2, and the copper-based catalyst CZA-S3 was tested using a ZQJ-II intelligent particle strength testing machine. The mechanical strength refers to the radial crushing strength of the cylindrical catalyst. 20 complete samples were tested in each group to calculate their average crushing strength.
[0211] Among them, the average crushing strength of the copper-based catalyst CZA-3 provided in Example 3, the copper-based catalyst MCZA-5 provided in Example 9, the copper-based catalyst CZA-S1, the copper-based catalyst CZA-S2, and the copper-based catalyst CZA-S3 is as follows: Figure 3 shown.
[0212] Depend on Figure 3 The average crushing strengths of the three commercial catalysts, copper-based catalysts CZA-S1, CZA-S2, and CZA-S3, were 20.6 N / mm, 24.7 N / mm, and 31.8 N / mm, respectively. The average crushing strengths of the copper-based catalysts CZA-3 and MCZA-5 provided by the embodiments of the present invention were 28.4 N / mm and 37.5 N / mm, respectively. The average crushing strength of the copper-based catalyst MCZA-5 was 32.1% and 17.9% higher than those of the copper-based catalysts CZA-3 and CZA-S3, respectively.
[0213] Experimental Example 2
[0214] This experimental example is used to test the catalytic activities of the copper-based catalysts provided in Examples 1 to 11, copper-based catalyst CZA-S1, copper-based catalyst CZA-S2, and copper-based catalyst CZA-S3.
[0215] Experimental conditions: Copper-based catalyst evaluation experiments were conducted using a fixed-bed tubular reactor with an inner diameter of 20 mm, a tube length of 400 mm, and a constant temperature zone of 60 mm. The catalyst sample (20-40 mesh) weighed 5.4 g and had a volume of 5 ml.
[0216] Before the experiment, the catalyst was pre-reduced with a 5% H2 / N2 mixed gas, the reducing gas space velocity was 5000 / h, the pre-reduction temperature was 240℃, and the reaction time was 5h;
[0217] The gas flow rate after the reaction was tested by a wet flow meter (8GB-0.5), and the exhaust gas composition was analyzed by gas chromatography (GC6820).
[0218] Methanol steam reforming reaction (MSR): The water-to-alcohol ratio in the methanol aqueous solution is 1-2, the liquid phase space velocity is 0.5-2.5 / h, and the reaction temperature is 160-260°C.
[0219] Water gas shift reaction (WGS): inlet gas composition is 2.1% CO, 74.5% H2, and 23.4% CO2, H2O / (H2+CO2+CO) (steam-gas ratio) is 0.25, gas space velocity is 1000-2500 / h, and reaction temperature is 160-240°C;
[0220] Methanol autothermal reforming reaction (ATR): water-methanol ratio is 0-1.5, liquid phase space velocity is 1.0-3.0 / h, oxygen-methanol molar ratio is 0.3-0.6, and gas phase space velocity is 3000 / h.
[0221] The results show that the optimal conditions for the methanol steam reforming reaction are a reaction temperature of 220°C, a water-to-methanol ratio of 1.5, and a liquid phase space velocity of 1.5 / h. Under these conditions, the methanol conversion rates of the methanol steam reforming reaction catalyzed by the copper-based catalysts provided in Examples 1 to 11, copper-based catalyst CZA-S1, copper-based catalyst CZA-S2, and copper-based catalyst CZA-S3 are shown in Table 2.
[0222] The results showed that the optimal conditions for methanol autothermal reforming reaction were an oxygen-methanol molar ratio of 0.4, a water-methanol ratio of 1.5, and a liquid phase space velocity of 2.0 / h. Under these conditions, the reaction temperature reached 310°C, the methanol conversion rate of the copper-based catalyst MCZA-5 reached more than 99%, and the hydrogen yield was 2.5 mol / mol methanol. The reaction temperature, methanol conversion rate, and tail gas composition that can be achieved in the methanol autothermal reforming reaction catalyzed by the copper-based catalyst MCZA-5 under the conditions of a water-methanol ratio of 1.5, a liquid phase space velocity of 2.0 / h, and an oxygen-methanol molar ratio of 0.3-0.6 are shown in Table 3.
[0223] The results show that the optimal conditions for the water gas shift reaction are a reaction temperature of 200°C and a gas phase space velocity of 1500 / h. Under these conditions, the CO concentration at the reaction outlet of the water gas shift reaction catalyzed by the copper-based catalysts provided in Examples 1 to 11 is shown in Table 2.
[0224] As shown in Table 2, the methanol conversion rates of the methanol steam reforming reaction catalyzed by copper-based catalysts with copper-zinc molar ratios of 3:5, 4:4, 5:3, and 6:2 are compared. Among them, the copper-based catalyst CZA-3 (copper-zinc ratio of 5:3) has the best MSR activity.
[0225] As the replacement amount of activated alumina was gradually increased to 100%, the MSR activity of the copper-based catalyst first increased and then decreased. The catalytic activity of the copper-based catalyst MCZA-5 was optimal when the molar ratio of copper, zinc, and aluminum was 5:3:2. At the same time, the MSR catalytic activity of MCZA-5 was higher than that of the commercial catalyst and the copper-based catalyst CZA-S3, which indicates that MCZA-5 prepared by replacing aluminum nitrate with activated alumina particles as the catalyst precursor still has a high MSR activity.
[0226] Comparison of the outlet CO concentrations of several copper-based catalysts showed that all catalysts had the best water gas shift reaction activity at 200°C, among which the copper-based catalyst MCZA-5 had the lowest outlet CO concentration, indicating that its CO water gas shift activity was also higher than that of the two commercial catalysts, copper-based catalyst CZA-S1 and copper-based catalyst CZA-S2.
[0227] From Table 3, Figure 1 It can be seen that during the methanol autothermal reforming reaction, with the increase of the oxygen-methanol molar ratio, the reaction temperature and methanol conversion rate increase accordingly; the hydrogen concentration and yield first increase and then decrease, and reach the maximum value when the oxygen-methanol molar ratio is 0.4, with the hydrogen concentration reaching 47.0% and the hydrogen yield being 2.5 mol / mol methanol.
[0228] Experimental Example 3
[0229] This experimental example is used to test the catalytic stability of the copper-based catalysts MCZA-5, CZA-S1, and CZA-S2 provided in Example 9.
[0230] Experimental conditions: Copper-based catalyst evaluation experiments were conducted using a fixed-bed tubular reactor with an inner diameter of 20 mm, a tube length of 400 mm, and a constant temperature zone of 60 mm. The catalyst sample (20-40 mesh) weighed 5.4 g and had a volume of 5 ml.
[0231] Before the experiment, the catalyst was pre-reduced with a 5% H2 / N2 mixed gas, the reducing gas space velocity was 5000 / h, the pre-reduction temperature was 240℃, and the reaction time was 5h;
[0232] The gas flow rate after the reaction was tested by a wet flow meter (8GB-0.5), and the exhaust gas composition was analyzed by gas chromatography (GC6820).
[0233] Water gas shift reaction (WGS): The inlet gas composition was 2.1% CO, 74.5% H2, and 23.4% CO2, the H2O / (H2+CO2+CO) (steam-gas ratio) was 0.25, the gas space velocity was 1500 / h, and the reaction temperature was 200°C.
[0234] The copper-based catalyst MCZA-5 and two commercial catalysts, copper-based catalysts CZA-S1 and CZA-S2, maintained good WGS reaction activity during the 200-h operation of the catalytic water gas shift reaction. Figure 2 .
[0235] Table 1
[0236]
[0237]
[0238] Table 2
[0239] Catalyst name MSR methanol conversion rate, % CO outlet concentration of WGS, % CZA-1 73.6 0.560 CZA-2 97.4 0.286 CZA-3 99.5 0.212 CZA-4 98.4 0.264 MCZA-1 91.3 0.401 MCZA-2 95.6 0.299 MCZA-3 97.5 0.258 MCZA-4 90.8 0.236 MCZA-5 98.7 0.161 MCZA-6 95.9 0.201 MCZA-7 84.9 0.282 CZA-S1 - 0.505 CZA-S2 - 0.350 CZA-S3 96.6 -
[0240] Table 3
[0241]
[0242]
[0243] The embodiments described above are intended to better explain the present invention. It is not difficult for technical researchers in this field to make various modifications to these embodiments without departing from the principles and spirit of the present invention. Therefore, the present invention is not limited to the embodiments described herein. Any improvements or modifications made by those skilled in the art to the present invention based on the principles and spirit of the present invention should fall within the scope of protection of the present invention.
Claims
1. A method for preparing a copper-based catalyst, wherein: The preparation method comprises: A copper precursor, a zinc precursor, an aluminum precursor, and water are mixed to prepare a sol solution or a suspension; wherein the copper precursor is a copper metal salt, the zinc precursor is a zinc metal salt, and the aluminum precursor includes at least one of an aluminum metal salt and activated alumina particles; A first reagent is added to a sol solution or suspension, and then a first regulator is added to adjust the pH value of the solution to 2-8 to obtain a neutral solution; wherein the first reagent comprises at least one of citric acid, ammonium citrate, maleic acid, oxalic acid, and ammonium oxalate; the ratio of the molar amount of the first reagent to the sum of the molar amounts of copper, zinc, and aluminum is (1-3):1; and the first regulator comprises at least one of ammonia, ammonium carbonate, and ammonium bicarbonate; The neutral solution is heated to react to obtain a wet gel; the wet gel is then dried to obtain a xerogel; calcining the dry gel to obtain catalyst powder; The copper-based catalyst is obtained by pressure-casting the catalyst powder and then calcining it.
2. The preparation method according to claim 1, wherein Mixing a copper precursor, a zinc precursor, an aluminum precursor and water to prepare a sol solution or a suspension is achieved by one of the first, second and third methods; Method 1: copper metal salt, zinc metal salt and aluminum metal salt are added into water to form a sol solution; Method 2: copper metal salt, zinc metal salt, and aluminum metal salt are added to water to form a sol solution; activated alumina particles are added to the sol solution to obtain a suspension; Method 3: copper metal salt and zinc metal salt are added to water to form a sol solution; activated alumina particles are added to the sol solution to obtain a suspension.
3. The preparation method according to claim 1 or 2, wherein The copper metal salt includes one or a combination of two or more of copper nitrate, copper sulfate, copper chloride, copper citrate, and copper acetate; The zinc metal salt includes one or a combination of two or more of zinc nitrate, zinc sulfate, zinc chloride, zinc citrate, and zinc acetate; Aluminum metal salts include one or a combination of two or more of aluminum nitrate, aluminum sulfate, aluminum chloride, aluminum citrate, and aluminum acetate; The median particle size D of activated alumina particles 50 6.0μm-30μm.
4. The preparation method according to claim 1 or 2, wherein The molar ratio of copper, zinc and aluminum in the copper precursor, the zinc precursor and the aluminum precursor is 1:(0.33-1.67):(0.24-0.72).
5. The preparation method according to claim 1, wherein The temperature of the neutral solution for heating the reaction is 60-80°C.
6. The preparation method according to claim 1, wherein Based on the mass of the aqueous solution of the first reagent being 100%, the mass concentration of the first reagent in the aqueous solution of the first reagent is 15%-45%; The first regulator is added by adding an aqueous solution of the first regulator; based on the mass of the aqueous solution of the first regulator being 100%, the concentration of the first regulator in the aqueous solution of the first regulator is 7%-14%; The wet gel is dried at 100-110°C; During the calcination of the dry gel, the calcination temperature is 250-500°C; During the calcination process after the catalyst powder is die-cast and formed, the calcination temperature is 250-500°C.
7. The preparation method according to claim 1, wherein Catalyst powder die casting is achieved by: mixing the catalyst powder with water or polyvinyl alcohol solution to obtain a mixed material; The mixed material is die-cast into a shape.
8. The preparation method according to claim 7, wherein Based on the total mass of the polyvinyl alcohol solution being 100%, the concentration of polyvinyl alcohol in the polyvinyl alcohol solution is 1.5-4%; The mass ratio of the catalyst powder to water or polyvinyl alcohol solution is 1:(24-49).
9. A copper-based catalyst, wherein The copper-based catalyst can be prepared by the method for preparing the copper-based catalyst according to any one of claims 1 to 8.
10. Use of the copper-based catalyst according to claim 9 as a catalyst in methanol steam reforming, methanol autothermal reforming, and water gas shift reaction.